Capacity analysis of steel scaffolding decks - Robak, Aleksander (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The methods for numerical modelling and static computer analysis of steel decks fixed on scaffoldings are presented in this study. The main problem raised in the study is the presentation of the method of creating models of a single deck and determination of the suitability of every model for various project situations. Additionally, the comparison of the results obtained from a linear analysis and analysis with material nonlinearity is conducted.